2013
DOI: 10.1371/journal.pone.0054879
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Engagement Drives Differentiation of Human and Murine Dendritic Cells from a Pro- into an Anti-Inflammatory Mode

Abstract: The dendritic cell (DC) coordinates innate and adaptive immunity to fight infections and cancer. Our observations reveal that DCs exposed to the microbial danger signal lipopolysaccharide (LPS) in the presence of interferon-γ (IFN-γ) acquire a continuously changing activation/maturation phenotype. The DCs’ initial mode of action is pro-inflammatory via up-regulation among others of the signaling molecule interleukin (IL) 12, which polarizes IFN-γ secreting type 1 helper T-cells (Th1). Within 24 hours the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The binding of the pathogen-associated microbial pattern molecule LPS to Toll-like receptor (TLR) 4 on human MoDCs signals danger, which induces a potent immune stimulatory phenotype that is characterized by the release of IL-12p70 (18,19). Our finding that a pDC line activated with LPS is more active compared to unstimulated pDCs suggests that this TLR4 agonist plays a role in the activation of pDC functions (11).…”
Section: Discussionmentioning
confidence: 89%
“…The binding of the pathogen-associated microbial pattern molecule LPS to Toll-like receptor (TLR) 4 on human MoDCs signals danger, which induces a potent immune stimulatory phenotype that is characterized by the release of IL-12p70 (18,19). Our finding that a pDC line activated with LPS is more active compared to unstimulated pDCs suggests that this TLR4 agonist plays a role in the activation of pDC functions (11).…”
Section: Discussionmentioning
confidence: 89%
“…Different classes of PRRs were discovered in the last decades and include membrane anchored receptors such as toll-like receptors (TLRs) [ 9 ] and C-type lectin receptors (CLRs) [ 10 ], besides the cytoplasmic nucleotide-binding oligomerization domain- (Nod-) like receptors (NLRs), RIG-I-like receptors (RLRs), and AIM-2-like receptors [ 11 , 12 ], as well as a family of enzymes that function as intracellular sensors of nucleic acids, including OAS proteins and cGAS [ 12 ]. These PRRs are capable of triggering complex intracellular signals that stimulate DC maturation, increase the expression of major histocompatibility complex (MHC) and costimulatory molecules, and promote proinflammatory cytokines expression [ 13 , 14 ]. Thus, in a context of infection and inflammation, DCs can identify the presence of pathogens through PRRs and induce adaptive immune responses [ 13 ].…”
Section: Dendritic Cells and Their Role In The Induction Of Immunementioning
confidence: 99%
“…Most of the cytokines produced by moDC are released within the first 24 h [ 63 ]. In addition, we and others previously showed that in 6 h-matured DC the cytokine induction program is irreversibly primed [ 7 , 64 , 65 ]. Clinical trials employ diverse strategies to mature the DC.…”
Section: Importance Of Il-12: Is It All We Need?mentioning
confidence: 99%